2021
DOI: 10.3390/su13084500
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Mathematics and Science Teaching in the Context of Education for Sustainable Development: Design and Pilot Implementation of a Teaching-Learning Sequence about Air Quality with Pre-Service Primary Teachers

Abstract: This article presents an interdisciplinary teaching–learning sequence (TLS) about air quality for pre-service primary teachers using an organic learning garden. The design involved a curricular integration of concepts and competences about sustainability, mathematics, and science disciplines following constructivist and active learning strategies, such as problem-based learning and place-based education. In this TLS, both the topic and the learning context act as facilitators of education for sustainable devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In this systematic review of the literature, the science field (Ateş & Gul, 2018;Jegstad et al, 2018;Karaarslan Semiz & Teksoz, 2020;Hogan & O'Flaherty, 2021) and primary education field (Alvarez-Garcia et al, 2019;Malandrakis et al, 2019;Fuertes-Camacho et al, 2021;Rico et al, 2021) were found to be the most prevalent fields of study with 15% of percentage. Two studies recruited pre-service teachers who were education majors with a 7% of percentage (Colas-Bravo et al, 2018;Nousheen et al, 2020).…”
Section: Ro1: Common Fields Of Studies Involved In Preparing Pre-serv...mentioning
confidence: 86%
“…In this systematic review of the literature, the science field (Ateş & Gul, 2018;Jegstad et al, 2018;Karaarslan Semiz & Teksoz, 2020;Hogan & O'Flaherty, 2021) and primary education field (Alvarez-Garcia et al, 2019;Malandrakis et al, 2019;Fuertes-Camacho et al, 2021;Rico et al, 2021) were found to be the most prevalent fields of study with 15% of percentage. Two studies recruited pre-service teachers who were education majors with a 7% of percentage (Colas-Bravo et al, 2018;Nousheen et al, 2020).…”
Section: Ro1: Common Fields Of Studies Involved In Preparing Pre-serv...mentioning
confidence: 86%
“…New solutions and technologies will be needed, not only to mitigate the anthropic impact on the environment, but also to find solutions in the context of adaptation to the consequences of the anthropic activities themselves. Thus, knowledge, problem solving, understanding of sciences, and mathematical skills represent fundamental keys to support actions towards more sustainable societies [74][75][76]. These abilities will be needed by all the citizens in the near future, together with trans-disciplinary knowledge and soft skills [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…The case studies can be divided into three categories based on the level of digitalization their methods and tools used based on the SAMR model (Hamilton et al, 2016):  In some cases, there is no need to use technology further than to substitute or augment the already existing research and education tools to make the learning tools and the process more compatible with the younger generations (Maass et al, 2022;Rico et al, 2021;Songer and Ibarrola Recalde, 2021;Snell-Rood et al, 2021). It also makes research and education activities more easily conductive for technologically less developed institutions and communities (Gallay et al, 2021;Talley et al, 2021).…”
Section: Educational Tools For the Methodsmentioning
confidence: 99%
“…Therefore, this article and all the remaining publications (n=11) were specific case studies in which the application of certain problem-based and other learning tools and methods were used during the learning process. The subjects of the studies varied from 3rd-grade pupils to university students and pre-service teachers (Rico et al, 2021;Maass et al, 2022).…”
Section: General Characteristics Of Rq1mentioning
confidence: 99%
See 1 more Smart Citation